2013
DOI: 10.1007/s00268-013-2008-7
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study Using the Propensity Score to Clarify the Oncologic Feasibility of Thoracoscopic Esophagectomy in Patients with Esophageal Cancer

Abstract: TSE can contribute to prolonged survival after surgery in patients with esophageal cancer by enabling precise thoracic lymph node dissection based on a magnified surgical field. TSE might have maximum oncologic benefit and minimum invasiveness for patients with esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 48 publications
6
11
0
Order By: Relevance
“…The number of dissected recurrent laryngeal nodes was increased in the thoracoscopic approach group compared with the open thoracotomy group, as described in our previous report [20]. In addition, the feasibility of thoracoscopic esophagectomy in the prognostic analysis was suggested in previous reports, and it seems proper to use both data from open thoracic and thoracoscopic esophagectomy in the prognostic analysis [17,18,19,20]. While tumor location still had no significant prognostic impact by surgical approach group, the UE tended to show a more favorable prognosis in thoracoscopic surgery.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The number of dissected recurrent laryngeal nodes was increased in the thoracoscopic approach group compared with the open thoracotomy group, as described in our previous report [20]. In addition, the feasibility of thoracoscopic esophagectomy in the prognostic analysis was suggested in previous reports, and it seems proper to use both data from open thoracic and thoracoscopic esophagectomy in the prognostic analysis [17,18,19,20]. While tumor location still had no significant prognostic impact by surgical approach group, the UE tended to show a more favorable prognosis in thoracoscopic surgery.…”
Section: Discussionsupporting
confidence: 54%
“…Law et al [7 ]and Li et al [8] reported that the UE showed a less favorable prognosis compared with lower ESCC, because lymph node dissection around the tracheal tree and recurrent laryngeal nerve was difficult, and a more meticulous dissection of bilateral recurrent laryngeal nerve nodes might improve the prognosis. In addition, several recent reports have suggested that thoracoscopic esophagectomy might increase the number of harvested recurrent nerve nodes, and they argued that thoracoscopic esophagectomy provided a magnified field allowing more precise surgical manipulations [16,17,18,19,20]. Furthermore, positive recurrent laryngeal nerve nodes were observed more frequently in the UE group, as mentioned above.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The rate of open thoracotomies for the low GNRI group tended to be higher than that for the high GNRI group (46.4 vs. 28.7%; p = 0.108). Takeno et al [27] suggested that the method of open thoracotomy was limited for complete dissection, especially for upper mediastinal dissection. Therefore, it was thought that the number of lymph nodes dissected was significantly different between the high and the low GNRI group.…”
Section: Discussionmentioning
confidence: 99%
“…In many reports, the number of patients and the follow-up periods were insufficient to analyze the survival. However, recent studies, in which the surgical procedures were performed with the patient in a decubitus position at a single institution, have shown 5-year survival rates comparable to those for a historical control and OE [28,[71][72][73]. Yet, no studies have reported the long-term survival after MIE-PP, and the survival outcomes after MIE-PP and MIE-LP have not been compared.…”
Section: Technical Limitations Of Mie-ppmentioning
confidence: 84%